2010
DOI: 10.1177/0363546509351556
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the Unstable Ankle with an Osteochondral Lesion

Abstract: Simultaneous arthroscopic treatment of an OLT and open lateral ankle stabilization is a safe and effective procedure. The presence of an osteochondral lesion had a negative effect on the overall result when compared to that of patients who underwent lateral ankle stabilization as an isolated procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 36 publications
4
67
1
1
Order By: Relevance
“…Persistent pain and swelling may take longer to subside in the multiply injured ankle and limit the individual rehabilitation. Gregush and Ferkel [5] compared the ankle scores of surgically treated isolated chronic lateral ligament instability with instability together with an OCL. All their patients had an arthroscopy prior to a Broström anatomical repair.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent pain and swelling may take longer to subside in the multiply injured ankle and limit the individual rehabilitation. Gregush and Ferkel [5] compared the ankle scores of surgically treated isolated chronic lateral ligament instability with instability together with an OCL. All their patients had an arthroscopy prior to a Broström anatomical repair.…”
Section: Discussionmentioning
confidence: 99%
“…When reporting associated injuries, it is also important that any concomitant procedures performed be described, as they may affect overall outcomes and therefore must be considered. 11,26,34 In addition, numerous studies have demonstrated the importance of lesion size on clinical outcome, which likely has important long-term implications with respect to longevity of fibrocartilage. 12,28 Finally, whereas most studies reported the location of the lesion on the talus, most were reported only as a general description of medial or lateral.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in nearly 85% of sprains, the lateral ankle ligaments are affected [8,9]. Among these ligament injuries, the anterior talofibular ligament is the most affected [10], as it is injured in approximately 95% of ankle sprains [11]. Furthermore, this condition represents the most frequent ligamentous injury [12].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, this number drops to 15% after ligament suturing [17]. For both sutured and unsutured cases, however, there may be chronic ankle instability, impingement syndrome, or cartilage and talus osteochondral lesions with subsequent osteoarthritic joint degeneration [8,11]. Therefore, severe ankle injuries have to be treated properly to reduce long-term effect occurrences [2,5,7,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation